THE ROLE OF STRATEGIC MANAGEMENT IN HUMAN RESOURCES MANAGEMENT - pcadmin, Abd Alfatah Hasan (Scholar Express Journals, 2024)
A human resources are seen as a source of competitive advantage, so the investment in human resources has become more and more important. Fundamentally, strategic management of human resources helps a company to more completely satisfy its corporate and strategic objectives and to use its human resources to surpass a treatment as a normal organisational resource. Particularly with regard to changes in regional, national, and worldwide economies, strategic management is a process meant to let an organisation both define and implement a plan of action taking advantage of its competence and resources under changing market circumstances. Product, service, customer, competition, and most crucially organisational internal capability placement helps to accomplish this. Especially in fully utilising the synergies and contingency among activities and organisational resources and skills, the sequencing of policies, plans, and actions is vital within the flow of strategic management.
Keywords: competition; policies; actions; synergies